Modification of Factor VIII in Therapeutic Concentrates after Virus Inactivation by Solvent-Detergent and Pasteurisation - Raut, S.; Giambattista, Di M.; Bevan, S. A.; Hubbard, A. R.; Barrowcliffe, T. W.; Laub, R. (Thrombosis and Haemostasis, 1998)
The addition of a pasteurisation step to a solvent/detergent (SD) treated FVIII concentrate has recently resulted in enhanced inhibitor incidence in patients in Germany and Belgium. We have investigated the effect of virus inactivation procedures on FVIII function by preparing experimental concentrates from the same starting cryoprecipitate with the following procedures: none (N); dry heat (DH); pasteurisation (P); solvent/detergent (SD); solvent detergent + dry heat (SDDH); solvent detergent + pasteurisation (SDP). In addition, several clinical SD concentrates with and without pasteurisation were studied.There were no significant differences in fibrinogen and vWF content and in the ratio of one-stage/chromogenic FVIII activity among any of the samples studied. In thrombin proteolysis and FXa generation experiments, there were no differences in results on samples N, DH, P, and SDDH from those on sample SD. However sample SDP gave markedly different results from sample SD in the following respects: slower thrombin proteolysis (t½2 = 12.0 min vs 1.9 min); more rapid FXa generation (rate 2.5 times that of SD); enhanced phospholipid binding (KD = 3.89 × 10–11M vs 5.53 × 10–10M). Similar differences between SDP and SD were seen in the clinical samples.The observed changes in the FVIII activity occurred in combination with SD and pasteurisation, but not with either treatment alone. These results suggest that SDP treatment may enhance exposure of the phospholipid binding site in the C2 domain of FVIII, and since inhibitors to the SDP product are predominantly against C2, these findings could be relevant to the enhanced immunogenicity of the SDP product.